Role of School Environment in Enhancing Emotional Intelligence and Social Adjustment in Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2025)
We examine how Kerala's educational environment affects students' emotional intelligence (EI). The research analyzes how teenage stage, gender, and school environment affect emotional intelligence. It randomly and purposively selects 400 students from four CBSE-affiliated schools. EQ—"the capacity to manage, understand, and use emotions positively."—was measured using the Emotional Intelligence Scale. We assessed school atmosphere using the School Environment Inventory. Mid-puberty adolescents scored better on the EQ scale than late adolescents. Male students do somewhat better on emotional intelligence exams than female students, while the difference is not statistically significant. Middle adolescents express greater cognitive encouragement, inventiveness, and laxity in school than late adolescents. These variables improved EQ in both groups, although cognitive support and creative stimulation were most significant. But rejection and control have distinct effects. Rejection hurts emotional intelligence in late adolescence, whereas control boosts it throughout puberty. Analysis of variance (ANOVA) and Pearson correlation analysis demonstrate significant relationships between school environment and emotional intelligence. Regression study shows that school atmosphere affects pupils' emotional intelligence. This study emphasises the need of a secure learning environment for emotional intelligence development in Kerala, which has consequences for educational policy and curriculum. This research helps us understand how schools might help youngsters develop emotional resilience and social maturity by identifying environmental factors. This will aid their personal and social success.